Hypomagnesemia in intestinal lymphangiectasia: a case report and review of the literature - Hao Feng; Linfeng Zou; Xiao Zhai; Shengyu Zhang; Jingnan Li (BMC Gastroenterology, 2022)
Abstract Background Intestinal lymphangiectasia (IL) is a rare disease characterized by dilation of lymphatic vessels and leakage of lymphatic fluids into the intestinal lumen, causing depletion of lymphocytes, protein, lipids, fat-soluble vitamins, and electrolytes. Hypomagnesemia can occur in IL patients but is seldom discussed. Case presentation A 30-year-old Tibetan woman who had chronic diarrhea, edema, tetany, and tingling was diagnosed with IL. Prominent hypomagnesemia was noticed. She was treated with a medium-chain triglyceride (MCT) diet and nutrient supplementation with satisfactory results. We also present a systematic review of hypomagnesemia in IL cases from the published literature. Conclusions Hypomagnesemia may be an overlooked complication of IL, thus monitoring serum magnesium concentrations in IL patients is crucial.